2008
DOI: 10.1016/j.cbpa.2006.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Rewarming rates and thermogenesis in hibernating echidnas

Abstract: We measured body temperatures (T b ) in 14 free-ranging echidnas (Tachyglossus aculeatus) using implanted data-loggers. An average of 1020 ± 744 days of T b data was recorded from each animal. The average maximum T b was 35.3 ± 0.7°C (n = 14), and the lowest T b was 4.7°C. Detailed analysis of rewarming events from four echidnas showed rewarming time to be dependent on initial T b (rewarming time in hours = 15.6 − 0.41T initial , n = 31) with an average rewarming rate of 1.9 ± 0.4°C h − 1 . Based on an hourly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…There are no direct measurements of field metabolic rates (FMR) of platypuses, but FMR of short-beaked echidnas measured using the doubly labeled water method was 2.7 times the BMR (Green et al, 1992; Schmid et al, 2003). V˙O2 max for echidnas estimated from treadmill exercise (Edmeades and Baudinette, 1975) and from maximal rewarming rates from hibernation (Nicol and Andersen, 2008), is ~1.44 ml O 2 g −1 h −1 , 9 times the BMR, but only 28% of the value predicted for wild eutherian mammals of the same mass (Taylor et al, 1981). The highest metabolic rate recorded for platypuses is 1.9 O 2 g −1 h −1 when walking on a treadmill (Bethge et al, 2001), 4.2 times BMR, while the highest metabolic rates recorded while foraging in cold water are only 3.2 times BMR (Grant and Dawson, 1978; Bethge et al, 2001).…”
Section: Metabolic Rate and Body Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…There are no direct measurements of field metabolic rates (FMR) of platypuses, but FMR of short-beaked echidnas measured using the doubly labeled water method was 2.7 times the BMR (Green et al, 1992; Schmid et al, 2003). V˙O2 max for echidnas estimated from treadmill exercise (Edmeades and Baudinette, 1975) and from maximal rewarming rates from hibernation (Nicol and Andersen, 2008), is ~1.44 ml O 2 g −1 h −1 , 9 times the BMR, but only 28% of the value predicted for wild eutherian mammals of the same mass (Taylor et al, 1981). The highest metabolic rate recorded for platypuses is 1.9 O 2 g −1 h −1 when walking on a treadmill (Bethge et al, 2001), 4.2 times BMR, while the highest metabolic rates recorded while foraging in cold water are only 3.2 times BMR (Grant and Dawson, 1978; Bethge et al, 2001).…”
Section: Metabolic Rate and Body Temperaturementioning
confidence: 99%
“…The factors that determine the equilibrium T b can be seen by rearranging the familiar Scholander-Irving model (Nicol et al, 2008): Tb=Ta+V˙O2C i.e., T b falls to a temperature dependent on ambient temperature plus an amount determined by the ratio of hibernating metabolic rate to conductance. This relationship only holds for thermoconforming animals above the lower set point (Geiser, 2001; Nicol and Andersen, 2008). If T b drops below the set point, most hibernators increase heat production, which is energetically expensive (Geiser, 2004).…”
Section: Hibernationmentioning
confidence: 99%
“…Body temperature during hibernation Details of the timing and patterns of hibernation based on some of these data have been published previously (Nicol and Andersen, 2002), as has an analysis of rewarming (Nicol and Andersen, 2007b). A comparison of the T b records with the various environmental measures obtained from the BoM station (air temperature and soil temperature at 10, 20 and 50·cm) showed that, during hibernation, T b varied in parallel with soil temperature at 20·cm, although the absolute difference between the records would sometimes change.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…Over the last 10 years we have studied hibernation in free-ranging echidnas in the field using implanted T b data-loggers, and have collected a very large data set of more than 39 echidna years of data from 14 animals. We have previously analysed parts of this data set data to examine the relationship between T b and hibernation bout length (Nicol and Andersen, 2000), the timing and patterns of hibernation (Nicol and Andersen, 2002), and rewarming rates and thermogenesis (Nicol and Andersen, 2007b). These data show that during the hibernation season T b appears to follow T a quite closely.…”
Section: Introductionmentioning
confidence: 99%
“…Although metabolic rates during torpor can be reduced to as little as ∼1% of the basal metabolic rate in small species, energy expenditure during the entire hibernation season is usually ∼10-20% of that in active individuals because of the energetically expensive periodic arousals that consume most of the energy during the hibernation season (Wang 1978;Thomas et al 1990). Nevertheless, many hibernators can survive for months relying entirely on stored body fat (Willis 1982a;French 1985;Geiser et al 1990;Nicol and Andersen 2007).…”
Section: Introductionmentioning
confidence: 99%